Parkinson Disease: review - Salih, Raad Othman (Technium BioChemMed, 2023)
Parkinson’s sickness (PD) is a neurodegenerative ailment precipitated by the death of a kind of neuron that plays an integral function in the production of dopamine in the brain. The pathophysiology of this sickness is based totally on the formation of alpha syncline folds that generate Lewy bodies, which are cytotoxic and minimize dopamine levels. Most pharmacological redress for PD goal alphasynuclein to limit the symptoms. However, the therapeutic method to this pathology includes combination of pharmacological and non-pharmacological strategies to maximize results and improve symptomatological manipulate in these patients. It is therefore essential to delve deeper into the pathophysiology of the ailment in order to enhance these remedies and consequently the exceptional of life of the patients. Therefore, we urgently want to analyze every cutting-edge clinical trial’s status and therapeutic approach to find out new therapeutic tactics for PD treatment. We hope this evaluate can supply new ideas and insights for PD remedy development.